The influence of genetic factors on sports performance - Yüce, M. (Current academic studies in sport sciences - 2018, 2018)
The purpose of this review is to summarize the effect of genetic factors, especially ACE, ACTN3 and HIF1A genes, on sportive performance and to review new approaches for future studies in the field.